1049. SORBUS BRISTOLIENSIS: Rosaceae. (22nd December 2022) - Rich, Tim C. G.; Houston, Libby; Wray, Nicholas; King, Christabel; Brown, Andrew P.; Fay, Michael F.
Summary: Sorbus bristoliensis, BRISTOL WHITEBEAM, is described and illustrated. The history of the discovery and the origin of this narrow endemic are discussed. Notes on propagation and cultivation are also included.